Approach to the Evaluation and Management of Wide Complex Tachycardias. - Patrick Lam; Samir Saba (Indian Pacing and Electrophysiology Journal, 2002)
Wide complex tachycardia (WCT) refers to a cardiac rhythm of more than 100 beats per minute with a QRS duration of 120 ms or more on the surface electrocardiogram (ECG). It often presents a diagnostic dilemma for the physician particularly in determining its site of origin, which can be ventricular or supraventricular. In one series, only 32% of clinicians correctly diagnosed ventricular tachycardia (VT) in patients who presented with WCT1. Prompt diagnosis of the etiology of WCT is, however, essential since immediate care is frequently required. Diagnostic and therapeutic errors can produce poor outcome especially when ventricular tachycardia is not recognized.2,3 WCT that is grossly irregular typically represents atrial fibrillation with aberrant conduction or preexcitation. If its rate exceeds 200 beats per minute, the likelihood of atrial fibrillation with conduction over an accessory pathway should be entertained. In this article, we will discuss the approach to the evaluation and management of regular WCT.